Los tatuajes votivos y su eficacia en el Culto a la Santa Muerte. - Yllescas, Adrián; Kristensen, Regnar (Hermenéutica, 2026)
The devotion to Santa Muerte became publicly visible in central Mexico around the turn of the millennium. While academic research often focuses on the social dimensions of marginalized devotees who view the cult as a form of resistance against an oppressive society, the primary concern for devotees is guidance on how to approach the Saint, ask for favors, and offer retribution. This study adopts the exchange of gifts (dones) as its core analytical focus, aligning with the perspective of the devotees themselves. Based on qualitative ethnographic fieldwork, including semi-structured interviews in Mexico City, this article identifies three cultural modes of ritual gift exchange: domestic altars, mobile altars (temporary public setups), and body altars. The votive tattoo is introduced as the most intimate and committed type of altar. Drawing on the classical theories of the Gift by Mauss and Godelier, the tattoo is analyzed as a ritual corporeal deposit through which believers fulfill their commitment to SM following her intervention in critical life circumstances (e.g., health crises, legal issues, or economic precarity) or an oniric request.